2018
DOI: 10.1113/ep087006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of losartan and allopurinol on cardiorespiratory regulation in obstructive sleep apnoea

Abstract: Chemoreflex sensitization produced by chronic intermittent hypoxia in rats is attenuated by angiotensin II type 1 receptor (AT R) blockade. Both AT R blockade and xanthine oxidase inhibition ameliorate chronic intermittent hypoxia-induced endothelial dysfunction. We hypothesized that treatment with losartan and allopurinol would reduce chemoreflex sensitivity and improve hypoxic vasodilatation in patients with obstructive sleep apnoea. Eighty-six hypertensive patients with apnoea-hypopnoea index ≥25 events h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…The present analysis is based on data collected during a previously reported randomized clinical trial (NCT01637623) of the effects of allopurinol, losartan and placebo on chemoreflex sensitivity in hypertensive patients with OSA (Morgan et al . 2018). The majority of data reported herein were obtained at the initial (pre‐randomization, prior to drug treatment) visit to the laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present analysis is based on data collected during a previously reported randomized clinical trial (NCT01637623) of the effects of allopurinol, losartan and placebo on chemoreflex sensitivity in hypertensive patients with OSA (Morgan et al . 2018). The majority of data reported herein were obtained at the initial (pre‐randomization, prior to drug treatment) visit to the laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of carotid chemoreflex sensitivity has received recent attention in clinical conditions such as hypertension (Tafil-Klawe et al 1985), heart failure (Schultz et al 2007) and obstructive sleep apnoea (OSA) (Narkiewicz et al 1999a), and also in the context of acclimatization to high altitude hypoxia (Dempsey et al 2014). A variety of transient and steady-state stimulatory and inhibitory interventions (Narkiewicz et al 1999a;Leuenberger et al 2001;Steinback et al 2009;Sinski et al 2014;Morgan et al 2018;Phillips et al 2018;Keir et al 2019) have been employed to provoke measurable increases and decreases in ventilation and sympathetic outflow; however, limited information is available on whether ventilatory and neurocirculatory responses to carotid chemoreceptor stimulation and inhibition are associated in human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The exaggerated lumbar sympathetic and MAP responses to breath hold following chronic intermittent hypoxia were attenuated by losartan, an effect likely mediated by blunted upregulation of AT 1 R expression on the carotid body (Marcus et al, 2010). In contrast, losartan does not influence the ventilatory response to step changes in normocapnic hypoxia in patients with OSA (Morgan et al, 2018). In agreement with our findings, this indicates an alternative mechanism involved in chemoreceptor sensitization that is independent of the AT 1 R. For example, heart failure models suggest a reduction in carotid body blood flow is necessary to reduce neural nitric oxide synthase expression while elevating carotid body AT 1 R expression and ANG-II concentration (Li and Schultz, 2006).…”
Section: Influence Of At 1 R Blockade On the Hypercapnic And Voluntarmentioning
confidence: 86%
“…Translational findings in humans are currently limited. However, in a recent clinical trial, it was observed that losartan reduced systolic and diastolic blood pressure in OSA patients without modifying muscle-sympathetic outflow or ventilation during hypoxia [ 102 ]. OSA was fairly well established in these patients and as such, there may have been irreversible epigenetic remodeling of CB function [ 103 ], accounting for the apparent lack of impact of losartan on CB function.…”
Section: G αQ -Protein-coupled Receptor Signalimentioning
confidence: 99%